PENGARUH PENAMBAHAN PATI JAHE HASIL SAMPING PEMBUATAN JAHE INSTAN PADA MUTU KUE KERING - Hartati, M. E (UPN VETERAN JAWA TIMUR, 2012)
The study aims to determine effects of the adddition of ginger starch byproduct from instant ginger production on cookies quality produced. Research carried out by using a mixture of 85 % flour and 15 % starch ginger (treatment A), a mixture of flour 80 % and 20 % starch ginger (treatment B) and a mixture of 75 % flour and 25 % starch ginger (treatment C) From the results showed that the mixture of flour and ginger starch byproduct of making instant ginger did not significantly affect the color, flavor and texture of the resulting cookies, while the aroma of real effect. Treatment of a mixture of flour and ginger starch byproduct of making instant ginger cookies are preferred for the consumer is in treatment C, with chemical and microbiological test results on average were: water content of 1.79% w / w, ash content 0.97 % w / w, protein 7.89% w / w, Total Number Plate 6.9 x102 colonies / g. While the results of organoleptic tests averaged: color 3.20 (usual), taste 3.70 (like), aroma 3.90 (like) and texture 3.80 (like).Keywords: ginger starch, cookies